A Low-FODMAP Diet in the Management of Children With Functional Abdominal Pain Disorders: A Protocol of a Systematic Review. Issue 2 (30th May 2021) - Stróżyk, Agata; Horvath, Andrea; Szajewska, Hania
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The available interventions for the management of children with functional abdominal pain disorders (FAPD) are limited. A diet low in fermentable oligosaccharides, disaccharides monosaccharides, and polyols (FODMAPs) is widely used in adults and children with FAPD, despite limited available evidence. We aim to systematically review evidence on the efficacy and safety of using a low-FODMAP diet for the management of children with FAPD. Methods: The Cochrane Library, EMBASE, and MEDLINE databases will be searched for randomized controlled trials (RCTs) that compare the use a low-FODMAP diet (preferably a 3-step low-FODMAP diet but also only a strict low-FODMAP diet or restriction of individual FODMAPs) with any comparator (i.e., standardized [i.e., average national] or other diet or no intervention) in children with FAPD (regardless of the definition). Each FAPD and each low-FODMAP diet or individual FODMAP restriction will be assessed separately. The Cochrane Collaboration's tool for assessing the risk of bias will be used. The primary outcome will be the abdominal pain intensity. The secondary outcomes will be abdominal pain frequency, stool consistency, other gastrointestinal symptoms, school performance, and psychological functioning associated with FAPD, parent's work absenteeism associated with FAPD of a child, health-related quality of life, compliance, growth, and adverse events. The findings will be published in a peer-reviewed journal and submitted to relevant conferences. Conclusion: This systematic review of rigorous methodological design will update current evidence on the efficacy and safety of using a low-FODMAP diet. However, it may be limited by the quality of the included studies.